Supporting collaborative policy processes with a multi-criteria discussion of costs and benefits: The case of soil subsidence in Dutch peatlands - van Hardeveld, H. A.; Driessen, P. P.J.; Schot, P. P.; Wassen, M. J. (Elsevier Ltd, 2018)
Collaborative policy processes are increasingly advocated to resolve management problems of social-ecological systems. To elucidate which approaches work in diverse situations, this paper demonstrates the added value of Cost-Benefit Analysis in combination with a deliberative tool as a support system a collaborative policy process in Dutch peatlands. We used quantitative models to assess the spatial and temporal physical effects of three water management strategies steering soil subsidence and land use. The stakeholders involved in the case study provided empirical economic data to link the physical effects to the ensuing economic effects, which we distributed among the stakeholder groups affected. The case study aimed for an intersubjective assessment of strategies for water management and land use planning. We therefore enhanced the discursive features of Cost-Benefit Analysis, focusing on knowledge exchange and the evaluation of equitable tradeoffs. The stakeholders participating in our case study appreciated the approach´s comprehensive assessments, and the ensuing multi-criteria discussion of the costs and benefits. We believe this result can be attributed to (a) the clear, participatory design of the CBA process, (b) a comprehensive presentation of the constituent elements of the CBA result, and (c) the abundant opportunities to deliberate the results. We discuss how our approach can increase stakeholders’ capacity to understand the complexities of social-ecological systems and their ability to explore the potentialities of these systems.
Keywords: Collaborative policy processes; Cost-Benefit Analysis; Peatlands; Soil subsidence; Sustainable water management; Taverne; Forestry; Geography, Planning and Development; Nature and Landscape Conservation; Management, Monitoring, Policy and Law; SDG 15 - Life on Land